THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND TEACHER DISCIPLINE ON TEACHER PROFESSIONALITY THROUGH TEACHER JOB SATISFACTION AT SMPN 1 SERBA JADI - Dara Mustika Saragih; Gangsar Mayang Sari; Mangasi Sinurat; Nursaimatussaddiya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of Teacher Discipline and Transformational Leadership on Teacher Job Satisfaction and Teacher Professionalism in schools. Using a quantitative approach with path analysis, the results of the study indicate that Teacher Discipline has a significant influence on Teacher Job Satisfaction and Teacher Professionalism, both directly and through job satisfaction channels. In addition, Transformational Leadership also has a significant influence on both variables, although slightly lower than teacher discipline. Teacher Job Satisfaction acts as a mediator between teacher discipline and transformational leadership with teacher professionalism. This finding confirms the importance of the role of discipline and transformational leadership in improving teacher professionalism through increasing job satisfaction. This study suggests that schools focus more on developing supportive discipline and leadership and creating a work environment that improves teacher satisfaction and professionalism.